The effect of Internal Audit on the quality of Financial Statements of Medan City Government (Case Study on Medan City Inspectorate) - Pintgel Lovisa (Jurnal Ekonomi, 2022)
This research supposed to determine the effect of Internal Audit on the quality of financial statements Medan City Government (Case Study on Medan City Inspectorate). This type of research is quantitative research, the location of the study was conducted at the Medan City Inspectorate Office, population and sample in this study amounted to 32 people. Data collection techniques using questionnaires, data analysis techniques using validity test, simple regression test and hyptosis test. The results of this study found that the internal auditor variable has a positive and significant impact on the quality of the Financial Statements of the Medan City Government (Case Study at the Medan City Inspectorate) the results of the determination test above show that the coefficient of determination value of 0.715 this means that 71.5% of the variance in the value of, Education and long work.